My fair lady [videorecording] (Farmington Hills, Mich. CBS/Fox Video, 1984)
A linguistic professor bets a friend that he can turn a Cockney flower girl into a lady.
VHS.
Based on the musical play as presented on stage by Herman Levin.
From a play by Bernard Shaw.
Originally issued as a motion picture in 1964.
Director of photography, Harry Stradling ; art director Gene Allen ; film editor, William Ziegler ; lyrics, Alan Jay Lerner ; music, Frederic Lowe.
Audrey Hepburn, Rex Harrison.
Keywords: Musical films; Feature films